Physical mechanical, tribological, and thermal properties of new developed composites with Grewia optiva fiber and pan material. Issue 7 (25th May 2022) - Kumar, Naresh; Mehta, Vikas; Kumar, Sushil; Grewal, Jaswinder Singh; Ali, Safarat; Kashyap, Kamal; Kumar, Nitin; Devi, Seema
Abstract: This research article has developed a novel composite material using natural fiber and PAN fiber. The study aims to remove harmful materials from the composites on the market these days. Asbestos and aramid fiber has good properties and is used in those composites where good mechanical properties are needed. However, using these materials causes many environmental issues and harms humans and other animals. There are very rare studies of PAN and natural fiber based hybrid composites. So Grewia optiva, which has good mechanical properties, and PAN fiber, which has good tribological properties, has been used to develop composites. The percentages of both materials were taken (4–16 wt%) with other ingredients such as phenolic resin, G. optiva fiber, PAN fiber/Kevlar, and lapinus ceramic, potassium barium, titan, mica, and ceramic. The developed composites have shown physical, mechanical, and tribological properties.